Beyond the playlist: commercial radio as music culture. Issue 2 (19th June 2017) - Uimonen, Heikki
Abstract: This article presents the historical transformation of Finnish commercial radio popular music policies from 1985 to 2005 and contemplates the role of terrestrial radio in contemporary digital age. It argues that a sender-centred paradigm of early commercial radio was replaced swiftly by receiver-centred paradigm, which has been applied since the early 1990s. The change of radio music cultures is described in detail by dividing it into three different eras: Block Radio, Format Radio and Media Convergence . The study draws on the research project consisting of case studies analysing the music content of various radio stations. The primary empirical data is composed of 32 interviews of radio personnel and the analysis of 4, 500 individual songs broadcast by popular music radio stations with newspaper and journal articles supporting the primary data. Radio music culture is approached theoretically from the ethnomusicological perspective and thus defined as all practices that have an effect on broadcast music, including the processes of acquiring, selecting and governing music. The empirical results of the study show that the transformation of radio music cultures is affected by economic, technological, legal, organisational and cultural factors.